2023
DOI: 10.1158/1538-7445.agca22-b017
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B017: Epigenetic age in peripheral blood among children, adolescent, and adult survivors of childhood cancer

Abstract: Background: We have previously reported that epigenetic age acceleration (EAA) was associated with prior cancer treatment exposures and certain chronic health conditions (CHCs) among adult survivors of childhood cancer, but the early epigenetic aging pattern among children and adolescent survivors and its implication in CHCs, especially early-onset CHCs, remain to be explored. Methods: Expanded DNAm profiling with EPIC array for survivors in the St. Jude Lifetime Cohort covered the age <20 years (n=690 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In total, 22 studies were discovered meeting inclusion criteria for this review (Table S3). 19,40–60 …”
Section: Resultsmentioning
confidence: 99%
“…In total, 22 studies were discovered meeting inclusion criteria for this review (Table S3). 19,40–60 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that EAA based on DNAm PhenoAge was associated with specific cancer treatment exposures and chronic health conditions 16 and found different cross-sectional patterns of DNAm PhenoAge across chronological age-defined groups. 24 We derived the EAA by calculating the residual for each individual based on the least-squares regression of estimated DNAm PhenoAge against chronological age at blood draw for DNA sampling. The WGS data were generated using the HiSeq X Ten System (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…There is a notable lack of studies examining the longitudinal stability and change of MPSs in early childhood, because repeated measurements of DNA methylation in young children are still rare and the idea to examine biological aging in children is relatively new. Similarly, very few studies have explored the clinical relevance of MPSs in pediatric cohorts, though there is some evidence to suggest that they may, for example, help identify survivors of childhood cancer at increased risk for early-onset obesity, morbidity, and mortality 37 .…”
Section: Quantifying Biological Aging Early In the Life Spanmentioning
confidence: 99%